Non-profit Organizations: A Path for Social Economy - TOKER, KEREM; Toker K. (Istanbul University Publication, 2023)
The structural basis of the social economy is non-profit organizations. Therefore, understanding the structure and management principles of non-profits is essential to create a global economy based on solidarity. However, despite the critical importance and role of non-profit organizations, studies on non-profit organizations are not holistic from a managerial perspective. For this reason, a holistic approach that covers all economic, political, and social components is needed when analyzing the social economy and NPOs Toward this aim, in this section, nonprofits are examined based on their organizational structure and management principles. This examination will compare for-profit and non-profits organizations’ mission, organizational structure, performance criteria, etc. The lack of profit in non-profit organization’s (NPO) mission stands out as the most crucial difference that shapes their management characteristics and organizational structure.Keywords: Social Organizations, Social Economy, Organizational Structure, Non-profit Organizations
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Yönetim ve Organizasyon; Social Sciences and Humanities; Management; Management and Organization; Sosyal Bilimler (SOC); Ekonomi ve İş; YÖNETİM; İŞLETME; Social Sciences (SOC); ECONOMICS & BUSINESS; MANAGEMENT; BUSINESS; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; Pazarlama; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Marketing; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities